2016
DOI: 10.1124/mol.116.106765
|View full text |Cite
|
Sign up to set email alerts
|

The 2016 John J. Abel Award Lecture: Targeting the Mechanical Microenvironment in Cancer

Abstract: Past decades of cancer research have mainly focused on the role of various extracellular and intracellular biochemical signals on cancer progression and metastasis. Recent studies suggest an important role of mechanical forces in regulating cellular behaviors. This review first provides an overview of the mechanobiology research field. Then we specially focus on mechanotransduction pathways in cancer progression and describe in detail the key signaling components of such mechanotransduction pathways and extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 170 publications
0
13
0
1
Order By: Relevance
“…9,29,30 Indeed, BC progression, invasion, and resistance to chemotherapeutic drugs are not only determined by the tumor cells themselves, but also by the extracellular microenvironment. 31 Basic research studies have confirmed that the cross-linking collagen in the ECM plays an important role in tissue stiffness. 32 However, the reason why tumors with high stiffness tend to be resistant to NACT in BC remains unknown.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…9,29,30 Indeed, BC progression, invasion, and resistance to chemotherapeutic drugs are not only determined by the tumor cells themselves, but also by the extracellular microenvironment. 31 Basic research studies have confirmed that the cross-linking collagen in the ECM plays an important role in tissue stiffness. 32 However, the reason why tumors with high stiffness tend to be resistant to NACT in BC remains unknown.…”
Section: Discussionmentioning
confidence: 98%
“…In in vitro cultures mimicking stiffness changes during BC progression, alterations in ECM rigidity might aberrantly activate certain mechanotransduction pathways, resulting in various tumorigenic processes, such as sustained proliferation, EMT, invasion, metastasis, and resistance to cell death. 31,[45][46][47] However, alterations in ECM rigidity cannot be induced in the human body because cells normally exist in a physiologic environment with specific rigidity, pressure, and strain. Several studies have investigated whether markers such as HIF-1α, TWIST-1, and ITGB-1 can be used as therapeutic targets to reverse or block resistance to chemotherapy in BC.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix stiffness has been known to both instigate and mitigate proliferation, apoptosis, and angiogenesis, depending on the situation (Chin et al 2016). In addition, stiffer cancer extra-cellular matrix can promote tumor invasion including the epithelial-mesenchymal transition (transition toward migration, invasion, and death resistance) and increased proliferation (Leight et al 2012;Majeski and Yang 2016). At the same time, estimating forces in vivo can be difficult and/or costly which is why many have looked towards modeling to help estimate forces as cancer cells go through the various stages of metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…This symmetry results in high stability to deforming forces and efficient information transfer that helps maintain homeostasis. In cancer, this stability is greatly diminished, as cancer evolves to increasingly malignant forms [52][53][54][55]. The extracellular cell matrix also possesses tensegrity properties, which, when disrupted, may also contribute to degraded information transfer from the environment and increase metastatic potential [43].…”
Section: Geometric Symmetry Breakingmentioning
confidence: 99%